The Interactions of Social Norms about Climate Change: Science, Institutions and Economics - Antonio Cabrales; Manu García; David Ramos Mu\~noz; Angel Sánchez (Center for Economic Studies and ifo Institute (CESifo), 2022)
We study the evolution of interest about climate change between different actors of the population, and how the interest of those actors affect one another. We first document the evolution individually, and then provide a model of cross influences between them, that we then estimate with a VAR. We find large swings over time of said interest for the general public by creating a Climate Change Index for Europe and the US (CCI) using news media mentions, and little interest among economists (measured by publications in top journals of the discipline). The general interest science journals and policymakers have a more steady interest, although policymakers get interested much later.
Keywords: Q54; Q58; D85; A13; 330; climate change; social norms; text analysis; social networks